THEORETICAL AND METHODOLOGICAL FRAMEWORK FOR DEVELOPMENT OF CLIMATE RESILIENCE COMPETENCE IN ADOLESCENTS - Damian-Timoșenco, Gabriela (My University, 2020)
The research purpose resides in the theoretical and methodological argumentation for developing the climate resilience competence in adolescents.
Abstract of doctoral thesis in educational sciences - Thesis mentor: BODRUG-LUNGU Valentina,associate professor,PhD. habil. in pedagogy
Keywords: life competencies; climate change; gender-based; psycho-social resilience; climate-resilient adolescent; environmental challenges; experiential learning; integrative learning; values; behaviors